Efficacy of a Combination of N-Palmitoylethanolamide, Beta-Caryophyllene, Carnosic Acid, and Myrrh Extract on Chronic Neuropathic Pain: A Preclinical Study - Fotio, Yannick; Aboufares El Alaoui, Amina; Borruto, Anna Maria; Acciarini, Samantha; Giordano, Antonio; Ciccocioppo, Roberto (Frontiers in Pharmacology, 2019)
Neuropathic pain (NP) is a common public health problem that poses a major challenge to basic scientists and health-care providers. NP is a complex problem with an unclear aetiology and an often-inadequate response to current medications. Despite the high number of drugs available, their limited pharmacological efficacy and side effects hamper their chronic use. Thus, the search for novel treatments is a priority. In addition to pharmaceuticals, natural extracts and food supplements are often used to help to treat patients with NP. One such supplement is Noxiall®, a commercially available combination of N-Palmitoylethanolamide (PEA), beta-caryophyllene; carnosic acid and myrrh. Here, we compare the efficacy of Noxiall® to that of the medications gabapentin and pregabalin in the NP model of chronic constriction injury (CCI) using sciatic nerve ligation in the mouse. Following CCI, mice developed a significant increase in mechanical allodynia and thermal hyperalgesia. Results showed that administration of either Noxiall®, pregabalin or gabapentin significantly attenuated mechanical allodynia. The magnitude of the Noxiall® effect was comparable to that of gabapentin or pregabalin. In addition, co-administration of non-effective doses of pregabalin and Noxiall® resulted in a significant decrease in NP suggesting an additive efficacy. Noxiall® was efficacious also in reducing CCI-induced thermal hyperalgesia. These findings support the rationale of using natural remedies in conjunction with classical pharmacological agents to treat chronic NP.